Predictors of Communication Abilities of Children at Early Preschool Age - Vesela L. Milankov; Jelena P. Kerkez (University of Belgrade, Teacher Education Faculty, 2024)
This study aimed to investigate the predictors of preschool children's communication skills. The sample consisted of 84 children aged eighteen months to four years. Half of the sample consisted of children who were included in an institution for preschool education, while the other 50% of the children from the sample were not included in these institutions. Parents were surveyed using a questionnaire called the Language Use Inventory (O'Nell, 2009). Our results showed that the multiple linear regression models have an acceptable fit to the data and have a statistically significant proportion of the variance (R² = 0.83, p < 0.001). It was found that, of all the assumed variables, the length of involvement in PU, the number of gestures, words and sentences used by the child are good predictors that significantly explain children's communication abilities.